Hydrogel carrier with bubble vibration enhancer for ultrasound-triggered drug release - Ryuto Yamakawa; Hiroaki Onoe; Yuta Kurashina (Ultrasonics Sonochemistry)
Hydrogel-based drug carriers provide on-demand drug release via external stimuli. Ultrasound is a promising method because of the potential for remotely releasing the drug. However, intense ultrasound irradiation has been required in previous studies. This paper reports drug model release from hydrogel carriers encapsulating bubble vibration enhancers (BVEs) consisting of microbubbles coated with a lipid membrane. Vibration of BVEs induced by ultrasound stimulation promoted the release of drug models with ultrasound irradiation controlled to a biologically safe acoustic pressure based on spatial-peak temporal-average intensity (ISPTA). The release ratio increased significantly from 2.3 % without BVEs and ultrasound to 10.2 % with both. To evaluate the frequency response, the release ratio was measured at three different ultrasound frequencies (0.3, 1.8, and 2.5 MHz), showing increased efficiency as the frequency approached the resonance frequency of the BVEs. For in vivo applications, hydrogel microspherical carriers with BVEs achieved a 12 % release ratio. Poly-L-lysine coating successfully suppressed the drug release to 0.2 %. The carriers demonstrated repeated responsiveness when ultrasound was applied in three 5-minute intervals. The hydrogel carrier encapsulating BVEs we proposed is a promising in vivo device capable of releasing drugs on demand by ultrasound irradiation based on its high biosafety and acoustic responsiveness.